Sharon E. J. Gerstel (ed.). Viewing Greece: Cultural and Political Agency in the Medieval and Early Modern Mediterranean - Roussos, Konstantinos (Journal of Greek Archaeology, 2019)
The present volume is a collection of essays resulting from a number of events (conferences, classes, lectures) that took place in parallel to the exhibition Heaven and Earth: Art of Byzantium from Greek Collections (2013–2015). The exhibition was first presented in Washington, DC, then in Los Angeles, and finally, a reduced version travelled to Chicago.